2017
DOI: 10.3390/catal7090271
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Characteristics of New Antibacterials Based on Hexahistidine-Containing Organophosphorus Hydrolase

Abstract: Catalytic characteristics of hexahistidine-containing organophosphorus hydrolase (His 6 -OPH) and its enzyme-polyelectrolyte complexes with poly-L-glutamic acid or poly-L-aspartic acid (His 6 -OPH/PLD 50 ), hydrolyzing organophosphorous compounds, and N-acyl homoserine lactones were studied in the presence of various antibiotics (ampicillin, gentamicin, kanamycin, and rifampicin). The antibiotics at concentrations below 1 g·L −1 had a negligible inhibiting effect on the His 6 -OPH activity. Mixed inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 34 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…Aflatoxin dialdehyde aldo-keto reductase AKR7A1 (Figure 2 [15,16], Table 1 [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]) was isolated from rat liver, and its structure in complex with NADP + was solved [59]. This enzyme is assumed to reduce both aldehyde groups of dialdehyde of hydroxy aflatoxin B 2a , forming from 8,9-dihydrodiol aflatoxin B 1 , resulted in dihydroxy derivative.…”
Section: Aflatoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aflatoxin dialdehyde aldo-keto reductase AKR7A1 (Figure 2 [15,16], Table 1 [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]) was isolated from rat liver, and its structure in complex with NADP + was solved [59]. This enzyme is assumed to reduce both aldehyde groups of dialdehyde of hydroxy aflatoxin B 2a , forming from 8,9-dihydrodiol aflatoxin B 1 , resulted in dihydroxy derivative.…”
Section: Aflatoxinsmentioning
confidence: 99%
“…Position and geometry of substrate binding was determined using molecular docking with Autodock Vina as described [15] (see Appendix A for details). Molecular surface of substrate was calculated using Gamess-US as described [16] and is shown as mesh. Within reaction scheme, OH-groups marked with blue are introduced by cytochromes, and oxygens marked with red are modified by AKR7A1.…”
Section: Figurementioning
confidence: 99%
“…Similarly, Huang and coworkers design selenium-containing trypsin mimics that increase the substrate binding capacity and stability of glutathione peroxidases [34]. Maslova and coworkers investigated how lactonase activity of organophosphorus hydrolases can be increased by producing enzyme-polyelectrolyte complexes with poly-L-glutamic acid or poly-L-aspartic acid and adding small concentrations of antibiotics [35].…”
Section: The Present Issuementioning
confidence: 99%
“…Hexahistidine-tagged organophosphorus hydrolase (His 6 -OPH) is one such enzyme. It was previously shown that His 6 -OPH, in addition to its high catalytic activity in the process of hydrolysis of a number of organophosphorous compounds, also has lactonase activity against a number of AHLs (Maslova et al, 2017a; Maslova et al, 2017b). It has been established that combinations of His 6 -OPH with β-lactam antibiotics provide an increase in the efficiency of action of both the enzyme and antibiotics (Maslova et al, 2017a; Maslova et al, 2017b; Aslanli, Lyagin & Efremenko, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that His 6 -OPH, in addition to its high catalytic activity in the process of hydrolysis of a number of organophosphorous compounds, also has lactonase activity against a number of AHLs (Maslova et al, 2017a; Maslova et al, 2017b). It has been established that combinations of His 6 -OPH with β-lactam antibiotics provide an increase in the efficiency of action of both the enzyme and antibiotics (Maslova et al, 2017a; Maslova et al, 2017b; Aslanli, Lyagin & Efremenko, 2018). These results reinforce the interest in studying the possibility of combining His 6 -OPH with other antibiotics characterized by different chemical properties and a spectrum of bacterial targets (Azzam & Algranati, 1973; Salmon, Watts & Yancey Jr, 1996).…”
Section: Introductionmentioning
confidence: 99%